Hikayat Seri Kelantan: Pensejarahan Konflik dan Perang Saudara serta Pengukuhan Dinasti Long Yunus di Kelantan: Hikayat Seri Kelantan: A Historiography of Conflict and Civil War, and the Consolidation of the Long Yunus Dynasty in Kelantan - Nordin, Mardiana; Mohamed Hassan, Noraini; Ling, Ho Hui (Journal of Al-Tamaddun, 2024)
Using Malay manuscripts as historical sources is increasingly used by researchers. This study is significant, as Malay manuscripts were written not only by order of the king, but some of them were produces by the Malays, from their own lenses, experiences, and their own specific purposes. Therefore, the objective of this paper is to analyse the Hikayat Seri Kelantan as an important historical source in understanding the history of conflict and civil war in Kelantan during the 18th and 19th centuries. The next objective is to identify the consolidation of the Long Yunus Dynasty in Kelantan, even during the civil war period. This study uses the qualitative approach within the historical discipline. Through the library method, Hikayat Seri Kelantan is the main reference, alongside other sources. The period of study was the 18th and 19th centuries, from when Long Yunus was established as first ruler of Kelantan and when civil war broke out among his heirs. The findings highlighted key historical information regarding the founding of the kingdom of Kelantan from Hikayat Seri Kelantan. The study also proved that his descendants such as Long Muhammad, Long Tan and Long Senik Mulut Merah played significant roles in addressing internal conflict and consolidating their power over the throne of Kelantan.